Molecular simulations of cavitation bubble dynamics - Fu, Yuequn; Flekkøy, Eirik Grude (Frontiers in Physics, 2025)
We study the cavitation bubble that forms as a nano-scale spherical surface is detached from a flat surface using molecular dynamics (MD) simulations. This investigation maps the onset and early development stages of cavitation at the nanoscale. We study the effects of variable pulling speeds and ambient pressures on the dynamics of the vapor bubble. It was observed that a higher pulling speed increases the cavitation volume but reduces the bubble’s lifetime. On the other hand, ambient pressure variations significantly influence both the maximum volume and the collapse rate of the cavitation. The results are summarized in a phase diagram that displays the effects of these varying pulling speeds and ambient pressures. Significantly, the study corroborates a Family-Vicsek scaling law for the bubble volume evolution.